Inter and intra-tumor heterogeneity of paediatric type diffuse high-grade gliomas revealed by single-cell mass cytometry - Petrilli, Lucia Lisa; Fuoco, Claudia; Palma, Alessandro; Pasquini, Luca; Pericoli, Giulia; Grabovska, Yura; Mackay, Alan; Rossi, Sabrina; Carcaboso, Angel M.; Carai, Andrea; Mastronuzzi, Angela; Jones, Chris; et al. (Frontiers in Oncology, 2022)
Paediatric-type diffuse high-grade gliomas (PDHGG) are aggressive tumours affecting children and young adults, with no effective treatment. These highly heterogeneous malignancies arise in different sites of the Central Nervous System (CNS), carrying distinctive molecular alterations and clinical outcomes (inter-tumour heterogeneity). Moreover, deep cellular and molecular profiling studies highlighted the coexistence of genetically and phenotypically different subpopulations within the same tumour mass (intra-tumour heterogeneity). Despite the recent advances made in the field, the marked heterogeneity of PDHGGs still impedes the development of effective targeted therapies and the identification of suitable biomarkers. In order to fill the existing gap, we used mass cytometry to dissect PDHGG inter- and intra-heterogeneity. This is one of the most advanced technologies of the "-omics" era that, using antibodies conjugated to heavy metals, allows the simultaneous measurement of more than 40 markers at a single-cell level. To this end, we analyzed eight PDHGG patient-derived cell lines from different locational and molecular subgroups. By using a panel of 15 antibodies, directly conjugated to metals or specifically customized to detect important histone variants, significant differences were highlighted in the expression of the considered antigens. The single-cell multiparametric approach realized has deepened our understanding of PDHGG, confirming a high degree of intra- and inter-tumoural heterogeneity and identifying some antigens that could represent useful biomarkers for the specific PDHGG locational or molecular subgroups.